1996
DOI: 10.1002/(sici)1097-4628(19960110)59:2<287::aid-app13>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial design of the nonpolar polyolefin ternary composite with high strength, high toughness, and high modulus

Abstract: SYNPOSISAn interfacial model was proposed for the ternary thermoplastics (matrix)/elastomer/rigidparticle filler composite with high strength, high toughness, and high modulus. A dispersed phase of rigid particle as a core and elastomer as a shell that has a good interfacial adhesion with the matrix is the key point of the model. A composite with high strength, high toughness, and high modulus was obtained in the styrene (ST) and maleic anhydride (MAH) modified high-density polyethylene (HDPE)/ethylene-propyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The development of strong microcomposites requires to disperse homogeneously the particles in the material and to improve their bonding with the polymer matrix. One method to fulfill the latter condition is to introduce a rubbery phase into the composite with a morphology that is a rubber interphase forming core-shell structure [6]. Previous studies have shown that ethylene-octene copolymers (POE) have high tear resistance, which makes them good candidates as packaging materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The development of strong microcomposites requires to disperse homogeneously the particles in the material and to improve their bonding with the polymer matrix. One method to fulfill the latter condition is to introduce a rubbery phase into the composite with a morphology that is a rubber interphase forming core-shell structure [6]. Previous studies have shown that ethylene-octene copolymers (POE) have high tear resistance, which makes them good candidates as packaging materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To reach this goal, the design of the elastomer interlayer is crucial. Our work on high‐density polyethylene (HDPE)/ethylene–propylene–diene monomer (EPDM)/carbon black (CB) composites has shown that bad interfacial adhesion results in separated CB and EDPM phases in the HDPE matrix 16. When an interfacial modifier is used, CB is capsulated in EDPM, and this forms a core–shell structure.…”
Section: Introductionmentioning
confidence: 99%